2020
DOI: 10.1590/1678-4324-2020190184
|View full text |Cite
|
Sign up to set email alerts
|

Development and Characterization of Poly-ε-caprolactone Nanocapsules Containing β-carotene Using the Nanoprecipitation Method and Optimized by Response Surface Methodology

Abstract: Nanoparticles demonstrate an important role in the protection of bioactive compounds from external factors such as temperature, oxygen and light. In this study, poly-ε-caprolactone (PCL) nanoparticles entrapped β-carotene was produced using the nanoprecipitation method. Firstly, was evaluated the lipophilic surfactant effect and carrier agent of the active compound in the nanocapsules formulation. After choosing the most stable formulation, the nanocapsules production was optimized using β-carotene, caprylic/c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 17 publications
3
10
0
2
Order By: Relevance
“…The optimized HHC-CS-NPs show PDI values of less than 0.5, which are considered good particle size distributions. The results are in agreement with the study reported by Lino et al [ 47 ]. The morphology of the optimized HHC-CS-NPs visualized by TEM shows that they are spherical in shape and have a solid and dense structure ( Figure 2 a).…”
Section: Resultssupporting
confidence: 94%
“…The optimized HHC-CS-NPs show PDI values of less than 0.5, which are considered good particle size distributions. The results are in agreement with the study reported by Lino et al [ 47 ]. The morphology of the optimized HHC-CS-NPs visualized by TEM shows that they are spherical in shape and have a solid and dense structure ( Figure 2 a).…”
Section: Resultssupporting
confidence: 94%
“…PCL is known for yielding spherical nanocapsules with negative charge on the surface (Rahat et al., 2021 ). They displayed negative charges owing to PCL structure and its hydrophobic nature which may cause ionization of the carboxylic groups resulting in a negative potential to the interface (Michels et al., 2019 ; Lino et al., 2020 ). Therefore, increased concentration of PCL influences negativity of zeta potential of prepared nanocapsules.…”
Section: Resultsmentioning
confidence: 99%
“…The polymeric type (F1) of nanocapsules showed nearly two folds burst effect compared to the lipid type (F6) owing to deposition of some of the loaded amount of MN on the surface of PNCs (shell). Whereas, the LNCs may have offered more room for %DL in the core part due to the oily nature of LNCs core (Dubey et al., 2020 ; Lino et al., 2020 ). Another reason, suggested for the previously resulted release pattern of PNCs is the degradation of the thin polymeric outer shell membrane (Cauchetier et al., 2003 ).…”
Section: Resultsmentioning
confidence: 99%
“…As nanopartículas de poli-ԑ-caprolactona (PCL) foram preparadas pelo método de nanoprecipitação, conforme mencionado em Lino, R.C. e colaboradores (2020) 7 e com adaptações baseadas em Schubert, S. e colaboradores (2011) 8 (Figura 1). O polímero PCL, cedido pelo Instituto Granado de Tecnologia da Poliacrilonitrila -IGTPAN, foi previamente pesado e solubilizado em acetona em banho ultrassônico.…”
Section: Materiais E Métodosunclassified
“…Este método não requer taxas de cisalhamento/agitação estendidas, sonicação ou temperaturas muito altas, e é caracterizada por ausência de interfaces óleo-água 7 .…”
Section: Introductionunclassified